2021
DOI: 10.1002/chem.202101857
|View full text |Cite
|
Sign up to set email alerts
|

Combined Chemical Modification and Collision Induced Unfolding Using Native Ion Mobility‐Mass Spectrometry Provides Insights into Protein Gas‐Phase Structure

Abstract: Native mass spectrometry is now an important tool in structural biology. Thus, the nature of higher protein structure in the vacuum of the mass spectrometer is an area of significant interest. One of the major goals in the study of gas‐phase protein structure is to elucidate the stabilising role of interactions at the level of individual amino acid residues. A strategy combining protein chemical modification together with collision induced unfolding (CIU) was developed and employed to probe the structure of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“… The fact that proteins lacking basic residues favor the CRM over CEM reveals the limitations of using charge state signatures to assess the distribution of folded states . As a result, proteins with few ionizable groups may display diverging charging patterns upon unfolding. Previous studies have shown that point mutations can affect the CIU pattern of native-like protein ions by modulating their structure in solution. ,,, Our findings reveal that even identically folded proteins can exhibit different CIU fingerprints due to altered surface electrostatics during ESI. Because these differences arise from the locations of ESI charges, not from solution folding, care must be taken when using CIU data to probe solution structures. Gas-phase unfolding is routinely used to identify compounds that can stabilize protein complexes by occupying specific binding pockets. , We find that moving charged sites can have a dramatic effect on a protein’s conformation in the gas phase.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“… The fact that proteins lacking basic residues favor the CRM over CEM reveals the limitations of using charge state signatures to assess the distribution of folded states . As a result, proteins with few ionizable groups may display diverging charging patterns upon unfolding. Previous studies have shown that point mutations can affect the CIU pattern of native-like protein ions by modulating their structure in solution. ,,, Our findings reveal that even identically folded proteins can exhibit different CIU fingerprints due to altered surface electrostatics during ESI. Because these differences arise from the locations of ESI charges, not from solution folding, care must be taken when using CIU data to probe solution structures. Gas-phase unfolding is routinely used to identify compounds that can stabilize protein complexes by occupying specific binding pockets. , We find that moving charged sites can have a dramatic effect on a protein’s conformation in the gas phase.…”
Section: Discussionmentioning
confidence: 52%
“… Previous studies have shown that point mutations can affect the CIU pattern of native-like protein ions by modulating their structure in solution. 9 , 15 , 54 , 55 Our findings reveal that even identically folded proteins can exhibit different CIU fingerprints due to altered surface electrostatics during ESI. Because these differences arise from the locations of ESI charges, not from solution folding, care must be taken when using CIU data to probe solution structures.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…53 Separation of oligosaccharides resulted in a resolving power of approximately 120 using three passes, 54 while an estimated resolution of 920 could be achieved after 58 cycles. 55 Because of its outstanding efficiency, cyclic IMS was applied in various proteomics studies as well, both for peptide [56][57][58][59][60][61][62] and protein 27,[63][64][65][66][67][68][69] analysis. This technique was shown to provide more identified peptides resulting in increased sequence coverage.…”
Section: Introductionmentioning
confidence: 99%
“…64 It was demonstrated that cyclic IMS efficiently separates protein conformers 65,66 and is capable to monitor the extent of protein unfolding. 67,68 Further, protein conformational changes may occur upon (multipass) cyclic experiments depending on the voltage settings applied. 27,69 Establishing that cyclic IMS is indeed a highly relevant platform for our investigations, our aim with the present project is to formulate practical suggestions on choosing the best CE setting for proteomics if IMS is used.…”
Section: Introductionmentioning
confidence: 99%